Type-1 (CB1) cannabinoid receptor promotes neuronal differentiation and maturation of neural stem cells. - Claudia Compagnucci; Sara Di Siena; Maria Blaire Bustamante; Daniele Di Giacomo; Monia Di Tommaso; Mauro Maccarrone; Paola Grimaldi; Claudio Sette (PLoS ONE, 2013)
Neural stem cells (NSCs) are self-renewing cells that can differentiate into multiple neural lineages and repopulate regions of the brain after injury. We have investigated the role of endocannabinoids (eCBs), endogenous cues that modulate neuronal functions including neurogenesis, and their receptors CB(1) and CB(2) in mouse NSCs. Real-time PCR and Western blot analyses indicated that CB(1) is present at higher levels than CB(2) in NSCs. The eCB anandamide (AEA) or the CB(1)-specific agonist ACEA enhanced NSC differentiation into neurons, but not astrocytes and oligodendrocytes, whereas the CB(2)-specific agonist JWH133 was ineffective. Conversely, the effect of AEA was inhibited by CB(1), but not CB(2), antagonist, corroborating the specificity of the response. CB(1) activation also enhanced maturation of neurons, as indicated by morphometric analysis of neurites. CB(1) stimulation caused long-term inhibition of the ERK1/2 pathway. Consistently, pharmacological inhibition of the ERK1/2 pathway recapitulated the effects exerted by CB(1) activation on neuronal differentiation and maturation. Lastly, gene array profiling showed that CB(1) activation augmented the expression of genes involved in neuronal differentiation while decreasing that of stemness genes. These results highlight the role of CB(1) in the regulation of NSC fate and suggest that its activation may represent a pro-neuronal differentiation signal.